농업분야 소규모 협동조합 유통체계 구축을 위한 우선순위 평가 - 김창환; 황대용; Kim, Chang-Hwan; Hwnag, Dae-Yong (Journal of distribution science, 2015)
Purpose - Domestic cooperatives tend to increase during the establishment of cooperatives and gradually through the basic law of social needs. However, only cooperatives' qualitative grow this secured without blessings, and their quantitative growth through government support is questionable. The purpose of this study is to analyze the agricultural cooperatives established through the Distribution System Cooperatives Basic Law, which was enacted in January 2012. Subsequently, establishing agricultural cooperatives was done briskly. However, cooperatives established rapidly after the founding of the Basic Law encountered problems. Research design, data, and methodology - To assess the performance of selected agricultural cooperatives, data were analyzed using the methodological Analytic Hierarchy Process (AHP) approach. The AHP is a set of systematic procedures to hierarchically analyze the elements of any problem. Using a survey on expertise, a series of comparative determinations of each pair is performed to evaluate the relative strengths and the strengths of the impact between elements within the hierarchy. A survey was conducted on 10 small agricultural cooperatives using AHP analysis for the examination. The purpose of such research and analysis is to recommend a direction for future policies aimed at small agricultural cooperatives. Result - This study applied three types of policy evaluation criterion, including market expansions, organizations, and cooperative projects, and 12 types of small agricultural cooperative policy measures. Market expansion policies for agricultural cooperatives are classified into four categories: school meals, direct transactions, shopping malls, and wholesale markets. Organizational policies for agricultural cooperatives are classified into four types: existing sales channel management, education, preventing free riding, and enlarging members. Cooperative project policies in agricultural cooperatives are classified into four policy areas: cooperation between cooperatives, community contribution, joint businesses, and government links. In this paper, the growth priority in agricultural cooperative policies is analyzed by applying policy evaluation criteria on the basis of a survey on expertise. The priorities of the policy program are also analyzed using a decision analytic hierarchy process. The results indicate that market expansion is the most important policy evaluation criterion therefore, improving direct transactions, school meals, management of existing sales channels, and shopping malls are crucial policy measures. In contrast, the cooperation of cooperatives, expansion of union members, and cooperation with the government were found to have low priority. Conclusions - Agricultural cooperatives should develop plans as follows. Small agricultural cooperatives need to secure school meals and direct transactions for market expansion, restructure marketing strategies to manage existing sales channels, and, finally, increase education and training for sustainable organizational development. This study has the following limitations. Because the subject of the investigation is a new cooperative, determining its sustainable growth is difficult. Therefore, through analysis and a continuous study of cooperatives, future research is expected to show that modifying the direction of agriculture cooperatives is necessary.